Perception of risks and drug use in university nursing students, Arequipa, Peru - Urday Concha, Vicente Fidel (2018)
The objective of the present study was to have a first approximation about the prevalence of life, information, perceptions, and risk behaviors regarding the consumption of licit, illicit and medical drugs, according to sex, in nursing students. A quantitative, exploratory descriptive and cross-sectional, census-type study was performed. A standardized questionnaire of 241 items was applied and previously applied to 86 students of the third year of nursing at a private university in Arequipa Metropolitana. There were high prevalence of life for the consumption of licit substances, 84.4% for alcoholic beverages and 62.8% for tobacco, and for any illegal drug (31.4%), among which marijuana (17.1%), and cocaine (4.6%), with differences in consumption in favor of men, whereas in medical drugs the most commonly used substance is tranquilizers (19.8%), with differences in consumption favoring women. At the university, more than 93% of students received information to prevent drug use, and 34.8% reported having had sexual intercourse between one and several times under the influence of alcohol and illicit drugs. It is concluded that the results show the magnitude of the social problems of the consumption of licit, illicit and medical drugs among university students; In addition, there is a need to develop strategies for the promotion of health and prevention of psychoactive substances in the nursing career to reduce and prevent the prevalence of consumption among future professionals promoting healthy lifestyles, to ensure a better quality of life in the population.